1968
DOI: 10.1002/jsfa.2740190208
|View full text |Cite
|
Sign up to set email alerts
|

Effect of loaf specific volume on the rate and extent of staling in bread

Abstract: The quantitative relationships between loaf specific volume and the rate and extent of staling in bread as measured by changes in crumb elastic modulus have been examined. The results show that loaf specific volume is a major factor in determining both the rate and extent of staling, both of which decrease in a linear manner, over the range studied, as loaf volume increases. Only two factors have been found that have a significant influence on these curves, the basic breadmaking process and the storage tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
39
1

Year Published

1971
1971
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(48 citation statements)
references
References 0 publications
8
39
1
Order By: Relevance
“…These results were similar to those reported [19,22] who reported that breads with higher specific volume values had softer crumb texture. However, there are combined reports in the literature on sourdough fermentation and its effect on bread specific volume.…”
Section: Physical Characteristics Of Breadssupporting
confidence: 91%
“…These results were similar to those reported [19,22] who reported that breads with higher specific volume values had softer crumb texture. However, there are combined reports in the literature on sourdough fermentation and its effect on bread specific volume.…”
Section: Physical Characteristics Of Breadssupporting
confidence: 91%
“…It seems reasonable, therefore, to predict that CF bread will be initially firmer than CBP bread when freshly baked. Axford et al 16 have reported experimental data which tend t o support this prediction. …”
mentioning
confidence: 65%
“…Initial measurements were taken at the time of crumb cutting. The limiting value of crumb hardness (the highest possible value) was determined from the hardness of cut crumbs stored at 4.7℃ for 10 days, as reported by Axford et al (1968). The staling rate constant of breads (SRC) and the retrogradation rate constant of starch in breads (RRC) were obtained using the method developed by Yamauchi et al (2001).…”
Section: Dough Properties and Bread Evaluationmentioning
confidence: 99%